Bilateral spontaneous pneumothorax in a non-intubated COVID-19 patient - Frączek, Michał; Sklinda, Katarzyna; Walecki, Jerzy (Wiedza Medyczna, 2021)
Spontaneous bilateral pneumothorax is a rare condition occurring only in 1,3% of cases of spontaneous pneumothorax. Although spontaneous pneumothorax is recognized complication of COVID it is usually associated with severe cases of COVID pneumonia with massive lung involvement and a high level of inflammatory cytokines – so called "inflammatory storm". Large percentage of this patients requires life support with mechanical ventilation and pneumothorax is usually accompanied with pneumomediastinum. Nevertheless occurrence of spontaneous pneumothorax in non-intubated patients is very low. Therefore the presented case is exceptional in two ways – spontaneous pneumothorax occurred in non-intubated patient and is presented bilaterally. Early diagnosis of spontaneous bilateral pneumothorax can pose a diagnostic dilemma as it mimics progression of lung involvement in the course of COVID, pulmonary embolism or myocardial infarction. In our case apart from COVID pneumonia, patient had typical clinical presentation of myocardial infarction and known coronary artery disease, which initially mislead clinicians toward diagnosis of myocardial infarction (MI). However after exclusion of MI, chest radiograph was requested which revealed bilateral pneumothorax. The exact mechanism of pneumothorax development in non-intubated patients is not clear. Lung inflammation in COVID causes formation of pneumatocele, which can predispose to spontaneous pneumothorax. It is important to note that our patient developed pneumothorax without evident pneumatocele, underlying lung condition or history of trauma. This case shows that bilateral pneumothorax in COVID-19 can develop also in patients with only mild clinical course of COVID pneumonia. Early diagnosis and proper management is essential and can prevent life-threatening complications.